2017
DOI: 10.5781/jwj.2017.35.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Al-11.2Si Components by Direct Laser Metal Deposition for Automotive Applications

Abstract: Recently, Al-Si alloys samples have been manufactured at lab scale using various additive manufacturing processes, but so far there is no literature available to investigate the feasibility of fabricating Al-Si alloy component for automotive component applications using Direct Laser Metal Deposition (LMD) technique. This paper deals with the practical challenges of building single wall and block deposition (cuboid shapes) of eutectic Al-Si alloy using direct laser metal deposition process for developing automo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The Si peaks are broader, which results in the reduced size of the Si phase in fabricated samples. The results are similar to those already reported by other researchers [18][19][20][21]. However, no phase formation is observed for fabricated samples.…”
Section: Phase Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The Si peaks are broader, which results in the reduced size of the Si phase in fabricated samples. The results are similar to those already reported by other researchers [18][19][20][21]. However, no phase formation is observed for fabricated samples.…”
Section: Phase Analysissupporting
confidence: 92%
“…It can be clearly seen that the dendrites are homogenously distributed along the surface. The growth of the dendrites is not significantly high, which indicates that the material could potentially demonstrate reasonable ductile properties through an inverse relationship, a phenomenon explained by the classical theories of Spear and Gardner [18,19], while some argued that it could be a stepwise dependence on the scale of the dendritic structure. The Secondary Dendrite Arm Spacing (SDAS) is usually correlated with the cooling rate, which is expected to be on the order of 10 3 -10 5 K/s with LMD.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3b shows the concentration, the white bands being low-concentration regions between successive layers. Figure 4 shows the experimental results from Singh et al [52] where these key features are observed. The predicted features are quite typical of AM processing, and comparing figures 2d and 3b to figure 4, there is a qualitative agreement to experimental observations.…”
Section: Resultsmentioning
confidence: 92%
“…The SDAS can approximately indicate the cooling rate [20,21]. So the cooling rate in this study was calculated by the relationship of , where λ is the SDAS (µm), R is the average cooling rate (K/s) and α = 47, n = 0.33 for eutectic Al–Si alloys [18,22]. The different size of SDAS in fine dendrites zone and coarse dendrites zone is caused by the difference of cooling rate in the molten pool.…”
Section: Resultsmentioning
confidence: 99%
“…Javidani et al [21] deposited thin-wall parts with the height of about 14 mm with AlSi10Mg. Amrinder Singh et al [22,23] deposited single walls about 20 mm height with Al-11.2Si. Markus et al [34] optimised the energy input of individual tracks and parts with complex shape were built.…”
Section: Introductionmentioning
confidence: 99%